Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6ra05092a
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun gelatin nanofibers loaded with vitamins A and E as antibacterial wound dressing materials

Abstract: Illustration showing the fabrication process and test contents of electrospun gelatin nanofibers loaded with vitamins A and E as wound dressing materials in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 46 publications
(73 reference statements)
3
82
1
Order By: Relevance
“…Random and aligned fibers produced by electrospinning have been studied for different applications in the biomedical area, such as bone tissue engineering, vascular grafts, drug delivery, wound dressing, nerve regeneration, and so on. It is important to highlight that orientated fibers can influence cell adhesion, cell growth and modulate elongated cellular patterns that are typical of the morphology found in native tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Random and aligned fibers produced by electrospinning have been studied for different applications in the biomedical area, such as bone tissue engineering, vascular grafts, drug delivery, wound dressing, nerve regeneration, and so on. It is important to highlight that orientated fibers can influence cell adhesion, cell growth and modulate elongated cellular patterns that are typical of the morphology found in native tissues .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the possibility of using an electrospinning process to manufacture 3D scaffolds with tailorable fiber design (in terms of both diameter and distribution) as well as mechanical properties, other studies have considered the opportunity to use electrospun meshes as a vehicle to deliver bioactive factors (Hu et al, 2014;Sill & von Recum, 2008). Over the years, a number of drugs including antibiotics, anticancer drugs, as well as vitamins and proteins have been investigated as loading agents for the development of smart electrospun tissue engineering meshes, particularly for skin wound healing and bone tissue engineering applications (Huang, Branford-White, Shen, Yu, & Zhu, 2012;Li, Wang, Williams, et al, 2016;Lu, Jing, Song, & Wang, 2012;Sattary, Khorasani, Rafienia, & Rozve, 2018;Zahedi et al, 2012;Zhang et al, 2006).…”
Section: Electrospun Nanomaterials-based Meshesmentioning
confidence: 99%
“…To date, a variety of bioactive agents including antimicrobial agents, growth factors, genes, vitamins, metal, and metal oxide nanoparticles have been introduced into polymeric nanofibers for enhanced wound healing [12,21,22,26]. A recent study by Li et al [37] demonstrated the incorporation of vitamin A palmitate (VA) and vitamin E TPGS (VE), common derivatives of the unstable vitamins A and E into biodegradable GE nanofibers using electrospinning. The prepared nanofibers were studied for their sustained release behavior, antibacterial activity, cell proliferation, and in vivo wound healing performances.…”
Section: Natural Polymer Nanofibers As Wound Healing Scaffoldsmentioning
confidence: 99%